The use of the computed tomography in the diagnostic protocol of the elbow in the dog: 24 joints - Rovesti, Gian Luca; Biasibetti, Martina; Schumacher, Annette; Fabiani, Michelle (Veterinary and Comparative Orthopaedics and Traumatology, 2002)
The evaluation of the elbow joint is difficult based on clinical and radiographic examinations. The anatomical structures of its articular components are superimposed with standard radiography, often leading to presumptive diagnoses. When the radiographic findings become more suggestive, usually the early phase of the disease has passed and chronic disease has developed. Because computer-generated slices are not hindered by this superimposition, the use of computed tomography may be beneficial in investigating the joint. The purpose of this study was to evaluate if computed tomography could change or better define the diagnosis previously made on the basis of a radiographic examination in 12 client- owned dogs presented for elbow lameness. As a positive control, 12 out of the 24 imaged joints were surgically or arthroscopically explored. The diagnosis based on computed tomography was different or more precisely defined, compared to the radiographic examination, in 46% of the examined joints. Earlier and more complete definition of elbow joint disease may change the therapeutic options and, potentially, the clinical outcome.
Keywords: Dog; Elbow Joint; Computed Tomography